Schizophrenia-Related Neuregulin-1 Single-Nucleotide Polymorphisms Lead to Deficient Smooth Eye Pursuit in a Large Sample of Young Men - Smyrnis, Nikolaos (Oxford University Press, 2011)
Neuregulin-1 (NRG1) variations have been shown to modulate schizophrenia candidate endophenotypes related to brain structure and function. The aim of this study was to determine the effect of NRG1 on several oculomotor schizophrenia endophenotypes. The effects of 5 core single-nucleotide polymorphisms (SNPs) within the NRG1 gene to oculomotor parameters in a battery of oculomotor tasks (saccade, antisaccade, smooth eye pursuit, fixation) were investigated in a sample of 2243 young male military conscripts. Additive regression models, bootstrap and permutation techniques, were used as well as structural equation modeling and haplotype analysis. A deficit in global smooth eye pursuit performance measured using the root-mean-square error (RMSE) was related to the risk allele of SNP8NRG243177, and a deficit in global smooth eye pursuit performance measured using the saccade frequency was related with the risk allele of SNP8NRG433E1006. Structural equation modeling confirmed a global effect of NRG1 genotype on smooth eye pursuit performance using the RMSE, while the effect on saccade frequency was not confirmed. Haplotype analysis further confirmed the prediction from the structural equation modeling that a combination of alleles corresponding to the Icelandic high-risk haplotype was related to a deficit in global pursuit performance. NRG1 genotype variations were related to smooth eye pursuit variations both at the SNP level and at the haplotype level adding to the validation of this gene as a candidate gene for the disorder.